An activated persulfate catalytic membrane and a preparation method and application thereof
Patent Information
- Application Number
- CN202311707756.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-13
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-12-13
AI Technical Summary
但是,催化颗粒与膜之间的结合强度是影响膜稳定性的重要因素,催化颗粒会影响膜表面性状和孔隙大小,从而降低膜的过滤性能;而且,膜处理过程中,催化反应降解有机污染物的速率往往低于膜滤速率,这些成为催化膜实际应用的主要障碍
[0031]本发明通过提供聚乙二醇溶液和戊二醛溶液粘附剂将CuFeS2/Mxene催化材料粘附在PVDF薄膜上,加强了CuFeS2/Mxene催化材料和PVDF薄膜的结合强度,在较高的冲击下仍然能够减少CuFeS2/Mxene催化材料脱落。
Smart Images

Figure CN117815939B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of membrane treatment technology, specifically relating to an activated persulfate catalytic membrane, its preparation method, and its application. Background Technology
[0002] Moxifloxacin, a fourth-generation quinolone antibiotic, is commonly used to treat respiratory illnesses caused by susceptible bacteria. Moxifloxacin can be detected in ng / L levels in wastewater treatment plant influent, but conventional wastewater treatment processes are ineffective in removing it. Moxifloxacin has potential genotoxicity, and its release and accumulation in the environment threaten both ecology and human health. Therefore, there is an urgent need for an efficient water treatment technology to remove moxifloxacin.
[0003] Membrane separation technology is widely used in water treatment, food, pharmaceutical, and petrochemical industries due to its low energy consumption, lack of secondary pollution, simple operation, and high separation efficiency. However, membrane separation technology has low removal efficiency for small molecule pollutants; separating pollutants solely through physical methods cannot completely degrade them, requiring subsequent secondary treatment. In recent years, the combination of membrane technology and advanced oxidation technology has become one of the cutting-edge technologies in water treatment research. Catalytic membranes, obtained by combining catalysts with membranes, can achieve the dual functions of filtration and catalysis.
[0004] Membrane modification technology mainly has the functions of generating catalytic activity, enhancing hydrophilicity, and improving antibacterial properties. Modification methods are generally divided into two main categories: blending modification and surface modification. Among them, catalytic membranes prepared by surface modification have the dual functions of physical retention and chemical degradation, which can improve the removal efficiency of pollutants by membrane treatment and has attracted much attention in the field of water treatment. However, the bonding strength between catalytic particles and the membrane is an important factor affecting membrane stability. Catalytic particles can affect the surface properties and pore size of the membrane, thereby reducing the filtration performance of the membrane. Moreover, during membrane treatment, the rate of degradation of organic pollutants by catalytic reaction is often lower than the membrane filtration rate. These factors constitute the main obstacles to the practical application of catalytic membranes.
[0005] Persulfate activation technology offers advantages such as low storage and transportation costs, high free radical generation rate, and a wide range of activation methods. The sulfate free radicals generated during activation possess higher redox potentials and better reactivity than persulfate itself, enabling effective oxidative degradation of organic pollutants. In particular, persulfate (PMS) exhibits an asymmetrical charge distribution across its peroxy bond, allowing for effective activation via electron transfer, particularly in transition metals and carbon-based materials. Under activated conditions, persulfate demonstrates excellent degradation performance against antibiotics.
[0006] Therefore, there is an urgent need to design a catalytic membrane that can efficiently activate persulfate, and combine membrane separation technology and advanced oxidation technology to remove moxifloxacin pollutants in water, so as to achieve the dual role of physical interception and chemical degradation in the membrane treatment process. Summary of the Invention
[0007] This invention provides an activated persulfate catalytic membrane that can effectively perform both physical retention and chemical degradation, and has a good continuous removal effect on small molecule moxifloxacin.
[0008] This invention provides a method for preparing an activated persulfate catalytic membrane, comprising:
[0009] (1) CuFeS2 / Mxene catalyst material was ultrasonically dispersed in an aqueous solution to obtain CuFeS2 / Mxene solution. CuFeS2 / Mxene solution was poured into a polyvinylidene fluoride microporous filter membrane for vacuum filtration so that CuFeS2 / Mxene catalyst material was deposited on the polyvinylidene fluoride microporous filter membrane.
[0010] (2) Pour polyethylene glycol solution and glutaraldehyde solution sequentially onto the polyvinylidene fluoride microporous filter membrane with CuFeS2 / Mxene catalyst material deposited in step (1), press the membrane with nitrogen and dry it under vacuum to obtain an activated persulfate catalyst membrane.
[0011] This invention uses polyethylene glycol solution and glutaraldehyde solution as binders to firmly load CuFeS2 / Mxene catalytic material onto the surface of polyvinylidene fluoride microporous filter membrane (PVDF), increasing the bonding strength so that PVDF can not only retain moxifloxacin contaminants, but also prevent the loss of CuFeS2 / Mxene catalytic material.
[0012] Meanwhile, the CuFeS2 / Mxene catalytic material loaded on the PVDF membrane utilizes low-valence iron and copper to jointly activate persulfate. Sulfur can promote the valence cycle of iron and copper, while Mxene can induce interfacial electron transfer and chemical reconstruction of copper, promoting the reduction of high-valence copper in activated persulfate to low-valence copper. This avoids the continuous decrease in the rate of degradation of organic pollutants and ensures that the rate of catalytic degradation of moxifloxacin, an organic pollutant, reaches a balance with the membrane filtration rate.
[0013] Furthermore, the mass ratio of CuFeS2 to MXene is 4:1 to 9:1. By providing a suitable mass ratio of CuFeS2 to MXene, the activation process of persulfate by the CuFeS2 / MXene catalytic material achieves better Fe and Cu valence state cycling, thereby avoiding the decrease in chemical degradation rate during long-term pollution degradation and thus affecting the removal efficiency of moxifloxacin.
[0014] Furthermore, by controlling the mass ratio of CuFeS2 to MXene within this preferred range, the reaction rate of CuFeS2 / MXene catalytic material activating persulfate reached 0.0776–0.0944 min. -1 The removal efficiency of moxifloxacin reaches 99.1%-99.6%.
[0015] Furthermore, the loading of the CuFeS2 / Mxene catalytic material on the polyvinylidene fluoride microporous filter membrane is 2-4 mg / cm². 2 .
[0016] Furthermore, the pore size of the polyvinylidene fluoride microporous filter membrane is 50-100 nm. More preferably, the diameter of the polyvinylidene fluoride microporous filter membrane is 80 mm, and the effective loading area is 38.8 cm². 2 .
[0017] By controlling the loading of CuFeS2 / Mxene catalytic material, a suitable membrane filtration rate for moxifloxacin can be obtained by regulating the PVDF membrane pore size, while also loading an appropriate amount of CuFeS2 / Mxene catalytic material. This allows the rate of degradation of the organic pollutant moxifloxacin by the catalytic reaction to reach a balance with the membrane filtration rate, thereby enabling better and more effective removal of moxifloxacin.
[0018] Furthermore, the static pressure of the nitrogen gas is 0.05–0.20 MPa.
[0019] Furthermore, the preparation method of the CuFeS2 / Mxene catalytic material includes:
[0020] Ti3AlC2 was added to an etching solution of concentrated hydrochloric acid and LiF. After the reaction, centrifugation and vacuum drying were performed to obtain MXene. MXene, CuCl, FeCl3·6H2O, and (NH2)2CS were mixed and subjected to hydrothermal synthesis, followed by centrifugation and vacuum drying to obtain CuFeS2 / Mxene catalytic material. This invention prepares a highly efficient composite material CuFeS2 / Mxene for activating persulfate via hydrothermal synthesis.
[0021] Furthermore, the molar ratio of CuCl, FeCl3·6H2O, and (NH2)2CS is 1:1:2 to 2.5.
[0022] Furthermore, the hydrothermal synthesis reaction is maintained at a reaction temperature of 180–200°C for 10–12 hours, and vacuum drying is carried out at 60–70°C for 10–12 hours.
[0023] Furthermore, the concentration of the polyethylene glycol solution is 10-20 wt%, and the concentration of the glutaraldehyde solution is 10-20 wt%. This invention provides polyethylene glycol and glutaraldehyde solutions of suitable concentrations, enabling appropriate amounts of polyethylene glycol and glutaraldehyde to undergo an aldol condensation reaction to form a high-strength three-dimensional mesh structure, thereby firmly adhering the catalytic material to the PVDF surface. The volume of the polyethylene glycol solution is 25-50 mL, and the volume of the glutaraldehyde solution is 25-50 mL.
[0024] Furthermore, on the activated persulfate catalytic membrane obtained in step (2), a solution of polyethylene glycol (PEG, average relative molecular mass 600) and a solution of glutaraldehyde (GA, 50%) were added again, followed by vacuum drying. This was done to enhance the adhesion effect.
[0025] On the other hand, the present invention also provides an activated persulfate catalytic membrane, which is prepared according to the preparation method of the activated persulfate catalytic membrane.
[0026] On the other hand, the present invention also provides an application of an activated persulfate catalytic membrane in the removal of moxifloxacin, comprising: pouring a mixed solution of persulfate and moxifloxacin into the activated persulfate catalytic membrane, wherein the pH value of the mixed solution of persulfate and moxifloxacin is 3.10-10.89, and the applicable pH range of the solution is relatively wide.
[0027] The catalytic membrane provided by this invention degrades moxifloxacin through the following two aspects: first, the physical retention effect of the membrane, where the catalyst reduces the pore size of the PVDF membrane, and the membrane pores and the catalyst itself can adsorb a portion of the moxifloxacin; second, the oxidative degradation effect of activated persulfate, where CuFeS2 / MXene can efficiently activate persulfate to generate reactive oxygen species, degrading moxifloxacin in water and that retained by the membrane.
[0028] Furthermore, the concentration of the persulfate solution in the mixed solution of persulfate and moxifloxacin is 0.16-0.20 mM, the concentration of moxifloxacin is 1-3 mg / L, and the membrane pressure is 0.01-0.05 MPa.
[0029] A suitable concentration of persulfate solution can activate the catalytic membrane provided by the present invention to provide an appropriate amount of active material to remove a given concentration of moxifloxacin from the solution. By providing a suitable membrane pressure, the mixed solution can pass through the catalytic membrane, while avoiding excessively fast membrane rates that prevent the catalytic membrane from activating the persulfate and removing moxifloxacin.
[0030] Compared with the prior art, the beneficial effects provided by the present invention are as follows:
[0031] This invention provides a polyethylene glycol solution and a glutaraldehyde solution as adhesives to adhere CuFeS2 / Mxene catalysts onto a PVDF film, thereby strengthening the bond between the CuFeS2 / Mxene catalysts and the PVDF film and reducing the shedding of CuFeS2 / Mxene catalysts even under high impact.
[0032] Furthermore, by utilizing the metal valence state cycle of the CuFeS2 / Mxene catalytic material, the catalytic rate and the membrane filtration rate of PVDF are balanced, thereby improving the activation performance of the catalytic membrane for persulfate provided by this invention. Attached Figure Description
[0033] Figure 1 SEM image of the PVDF membrane provided in Example 1;
[0034] Figure 2 Here is an SEM image of the catalytic membrane prepared in Example 1;
[0035] Figure 3 The rate constant diagrams are shown for the catalysts prepared in Examples 1 and 2, and Comparative Examples 2, 4 and 5, in the experiment of removing moxifloxacin with activated persulfate.
[0036] Figure 4 The removal efficiency of moxifloxacin by the catalyst material (4:1) prepared in Example 1 in 5 cycles;
[0037] Figure 5 The mass change of the supported material of the catalytic membrane provided in Specific Embodiment 1 of the present invention under hydraulic shear.
[0038] Figure 6 A comparison of the removal efficiency of moxifloxacin by the catalytic membrane prepared in Comparative Example 1 and the PVDF membrane in Comparative Example 3.
[0039] Figure 7 This is a comparison chart showing the effect of the catalytic membranes prepared in Example 1 and Comparative Example 2 on removing moxifloxacin with the PVDF membrane in Comparative Example 3.
[0040] Figure 8 The removal efficiency of the catalytic membrane prepared in Example 1 for moxifloxacin under different pH conditions is shown. Detailed Implementation
[0041] The present invention will be further analyzed and described below with reference to specific embodiments. It should be noted that the embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above-described invention.
[0042] Example 1
[0043] (1) Prepare an etchant solution using 20 mL of HCl (9 mol / L) and 1 g of LiF. Slowly add 1 g of Ti3AlC2 and then magnetically stir the mixture at 45 °C for 24 hours. After the reaction is complete, wash the product with ultrapure water, centrifuging at 5000 rpm for 10 minutes each time, until the pH of the supernatant is approximately 5. Then, vacuum dry at 60 °C for 12 h to obtain dried MXene.
[0044] (2) 0.46 g of MXene was ultrasonically dispersed in 70 mL of ultrapure water. Then, 0.01 mol of CuCl, FeCl3·6H2O, and 10 mL of a solution containing 0.02 mol of (NH2)2CS were added sequentially. After magnetic stirring for 30 minutes, the solution was placed in a polytetrafluoroethylene-lined stainless steel autoclave and heated at 200 °C for 10 h. After the reaction, the product was washed with anhydrous ethanol and ultrapure water, respectively, and centrifuged at 5000 rpm for 10 minutes each time, repeating this alternating operation three times. Finally, the product was vacuum dried at 70 °C for 10 h to obtain CuFeS2 / MXene with a CuFeS2 to MXene mass ratio of 4:1.
[0045] (3) Fix the cleaned PVDF membrane (80 mm in diameter, average pore size 50–100 nm) in an ultrafiltration cup, and ultrasonically disperse CuFeS2 / MXene (4:1) in 50 mL of ultrapure water and pour it onto the filter membrane. Connect an external diaphragm pump and use vacuum filtration to rapidly deposit CuFeS2 / MXene onto the membrane, with a catalyst loading of 4 mg / cm³. 2 Then, 50 mL of 20 wt% polyethylene glycol (PEG) and 20 wt% glutaraldehyde (GA) were poured onto the membrane, and the membrane was vacuum-dried under nitrogen pressure at 0.05 MPa. On the dried catalytic membrane surface, polyethylene glycol (average relative molecular mass 600) and glutaraldehyde (50%) were added dropwise sequentially to induce a cross-linking effect. Finally, the membrane was vacuum-dried again to enhance adhesion, resulting in an activated persulfate catalytic membrane. Figure 1 and Figure 2 It can be seen that the PVDF membrane has a porous network structure with varying pore sizes; the pores between CuFeS2 / MXene particles are smaller than those in the PVDF membrane. Therefore, the loading of the catalytic material alters the original morphology of the PVDF membrane.
[0046] Example 2
[0047] (1) Prepare an etchant solution using 20 mL of HCl (9 mol / L) and 1 g of LiF. Slowly add 1 g of Ti3AlC2 and then magnetically stir the mixture at 45 °C for 24 hours. After the reaction is complete, wash the product with ultrapure water, centrifuging at 5000 rpm for 10 minutes each time, until the pH of the supernatant is approximately 5. Then, vacuum dry at 60 °C for 12 h to obtain dried MXene.
[0048] (2) 0.21 g of MXene was ultrasonically dispersed in 70 mL of ultrapure water. Then, 0.01 mol of CuCl, FeCl3·6H2O, and 10 mL of a solution containing 0.02 mol of (NH2)2CS were added sequentially. After magnetic stirring for 30 minutes, the solution was placed in a polytetrafluoroethylene-lined stainless steel autoclave and heated at 180 °C for 12 h. After the reaction, the product was washed with anhydrous ethanol and ultrapure water, respectively, and centrifuged at 5000 rpm for 10 minutes each time, repeating this alternating process three times. Finally, the product was vacuum dried at 70 °C for 10 h to obtain CuFeS2 / MXene with a CuFeS2 to MXene mass ratio of 9:1.
[0049] (3) Fix the cleaned PVDF membrane (80 mm in diameter, 50–100 nm in average pore size) in an ultrafiltration cup, and ultrasonically disperse CuFeS2 / MXene (9:1) in 50 mL of ultrapure water and pour it onto the filter membrane. Connect an external diaphragm pump and use vacuum filtration to rapidly deposit CuFeS2 / MXene onto the membrane, achieving a catalyst loading of 4 mg / cm³. 2 Then, 50 mL of 20 wt% polyethylene glycol and 20 wt% glutaraldehyde were poured onto the membrane, and the membrane was vacuum-dried under nitrogen pressure at 0.05 MPa. Polyethylene glycol (average relative molecular mass 600) and glutaraldehyde (50%) were then added dropwise to the dried catalytic membrane surface to induce a cross-linking effect. Finally, the membrane was vacuum-dried again to enhance adhesion.
[0050] Comparative Example 1
[0051] Unlike Example 1, the CuFeS2 / MXene loading is 2 mg / cm³. 2 .
[0052] Comparative Example 2
[0053] Unlike Example 1, the catalyst material is CuFeS2.
[0054] Comparative Example 3
[0055] Unlike Example 1, no catalyst material was loaded, and the PVDF membrane had a diameter of 80 mm and an average pore size of 50–100 nm.
[0056] Comparative Example 4
[0057] Unlike Example 1, 3.68 g of MXene was added and heated at 200°C for 10 h to obtain CuFeS2 / MXene material with a CuFeS2 to MXene mass ratio of 1:2.
[0058] Application examples
[0059] (4) Prepare 250 mL of an aqueous solution containing 2 mg / L moxifloxacin and 0.12 mM persulfate. Disperse CuFeS2 / MXene catalysts with mass ratios of 1:2, 1:1, 2:1, 4:1, 9:1, and 1:0 (0.12 g / L) using magnetic stirring. During the reaction, periodically remove samples, filter them through polyethersulfone (0.22 μm pore size), and immediately terminate the reaction by adding sodium thiosulfate. Determine the moxifloxacin concentration in the samples using high-performance liquid chromatography (HPLC).
[0060] like Figure 3 As shown, the mass ratio of CuFeS2 to MXene in the range of 4:1 to 9:1 exhibits a higher reaction rate for activating persulfate, indicating that CuFeS2 plays a dominant role in the activation of persulfate in the composite material, and that an appropriate MXene content is more conducive to exerting the synergistic effect of activating persulfate.
[0061] like Figure 4 As shown, the catalytic membrane prepared in Example 1 was reused 5 times, that is, step (4) was repeated 5 times using the catalytic membrane prepared in Example 1. During the 5 cycles, the degradation efficiency of moxifloxacin was high. Since the active sites on CuFeS2 / MXene adsorb pollutants and may also be covered by oxidation products, this weakens the activation of persulfate, causing the removal efficiency of moxifloxacin to decrease as the experiment progresses. However, in the 5th use, the removal rate of moxifloxacin was still 89.2%, indicating that CuFeS2 / MXene has good reusability. The composite material can still effectively activate persulfate under continuous use, which provides support for the catalytic membrane to activate persulfate for the removal of moxifloxacin.
[0062] like Figure 5As shown, the stability of the membrane composite material was determined by observing the mass change under hydraulic shear of the catalytic membrane prepared in Example 1, and catalytic membranes prepared with or without PEG and GA, with only 10 wt% PEG, or with only 20 wt% PEG, as different from Example 1. The initial mass m0 of the PVDF membrane and the catalytic membrane was recorded. Pure water was added to completely submerge the catalytic membrane, and mechanical stirring was performed at different speeds for 1 hour. After stirring, the catalytic membrane was removed, and the mass m' of the dried catalytic membrane was measured to calculate the mass change of the loaded material. Figure 5 As shown, CuFeS2 / MXene cannot be firmly bonded to the PVDF membrane by physical loading alone. However, the cross-linking effect generated by adding polyethylene glycol and glutaraldehyde enables the catalytic membrane to better resist the impact of water flow, ensuring the stability of the material loading.
[0063] like Figure 6 and Figure 7 As shown, the catalytic membranes prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were fixed on ultrafiltration cups, and 2 mg / L moxifloxacin aqueous solution and a certain concentration (0.12-0.20 mM) of permonosulfate (PMS) were poured in. The mixture was filtered under a pressure of 0.02 MPa. The total filtration volume of the moxifloxacin aqueous solution was 1.6 L. The filtrate was continuously collected during the process and the residual concentration of moxifloxacin in the sample was determined by high performance liquid chromatography. Figure 6 and Figure 7 The removal efficiency of moxifloxacin under different conditions was demonstrated. The CuFeS2 / MXene-supported catalytic membrane was superior to the CuFeS2-supported catalytic membrane, and appropriately increasing the persulfate concentration also enhanced the removal of moxifloxacin by the catalytic membrane. Compared with PVDF membrane treatment of moxifloxacin, using the catalytic membrane described in Example 1 with the addition of 0.20 mM persulfate increased the removal rate of moxifloxacin from 10.9% to 80.5%.
[0064] like Figure 8 As shown, the catalytic membrane prepared in Example 1 was fixed on an ultrafiltration cup. Each treatment involved 250 mL of a 2 mg / L moxifloxacin aqueous solution (the initial pH of the solution was adjusted to 3.10 or 10.89, and the initial pH of the moxifloxacin solution was measured to be 5.75) and 0.20 mM persulfate. The concentration of moxifloxacin in the filtrate was measured using high-performance liquid chromatography (HPLC). The solution was filtered six times at a pressure of 0.02 MPa. According to... Figure 8 The catalytic membrane-activated persulfate method showed good removal rates of moxifloxacin under both strong acid and strong alkaline conditions. The removal effect of this method on moxifloxacin was better under acidic conditions than under alkaline conditions.
Claims
1. The application of an activated persulfate catalytic membrane prepared by a method for removing moxifloxacin, characterized in that, include: (1) The CuFeS2 / Mxene catalyst was ultrasonically dispersed in an aqueous solution to obtain a CuFeS2 / Mxene solution. The CuFeS2 / Mxene solution was poured into a polyvinylidene fluoride microporous filter membrane for vacuum filtration so that the CuFeS2 / Mxene catalyst was deposited on the polyvinylidene fluoride microporous filter membrane. (2) Pour polyethylene glycol solution and glutaraldehyde solution sequentially onto the polyvinylidene fluoride microporous filter membrane with CuFeS2 / Mxene catalyst material deposited in step (1), press the membrane with nitrogen and dry it under vacuum to obtain an activated persulfate catalyst membrane; The concentration of the polyethylene glycol solution is 10-20 wt%, and the concentration of the glutaraldehyde solution is 10-20 wt%.
2. The application of the activated persulfate catalytic membrane prepared by the method described in claim 1 in the removal of moxifloxacin, characterized in that, The mass ratio of CuFeS2 to MXene is 4:1 to 9:
1.
3. The application of the activated persulfate catalytic membrane prepared by the method described in claim 2 in the removal of moxifloxacin, characterized in that, The activation rate of persulfate by the CuFeS2 / Mxene catalyst reached 0.0776–0.0944 min. -1 .
4. The application of the activated persulfate catalytic membrane prepared by the method described in claim 1 in the removal of moxifloxacin, characterized in that, The loading of the CuFeS2 / Mxene catalyst on the polyvinylidene fluoride microporous filter membrane is 2-4 mg / cm. 2 .
5. The application of the activated persulfate catalytic membrane prepared by the method described in claim 1 in the removal of moxifloxacin, characterized in that, The pore size of the polyvinylidene fluoride microporous filter membrane is 50-100 nm.
6. The application of the activated persulfate catalytic membrane prepared by the method described in claim 1 in the removal of moxifloxacin, characterized in that, On the activated persulfate catalytic membrane obtained in step (2), polyethylene glycol solution and glutaraldehyde solution are added again, and then the membrane is dried under vacuum.
7. The application of the activated persulfate catalytic membrane prepared by the method described in claim 6 in the removal of moxifloxacin, characterized in that, The concentration of the persulfate solution in the mixed solution of persulfate and moxifloxacin was 0.16–0.20 mM, and the permeabilization pressure was 0.01–0.05 MPa.
Citation Information
Patent Citations
MXene separation membrane capable of simultaneously separating oil and dye as well as preparation method and application thereof
CN112915816A
Method for degrading sulfamethoxazole in wastewater by activating persulfate with magnetic two-dimensional Mxene / CuFeO2 catalyst
CN114054059A